2017
DOI: 10.1038/s41598-017-10666-7
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping using an ultra-high-density SNP map reveals a major locus for grain yield in an elite rice restorer R998

Abstract: To dissect the genetic basis of yield formation in restorer line of hybrid rice, we conducted QTL analysis for 6 yield traits including panicles per plant (PPP), grains per panicle (GPP), grain yield per plant (GY), thousand-grain weight (TGW), above-ground biomass (AGB), and harvest index (HI) using SNP markers in a recombinant inbred lines (RILs) population derived from a cross between a tropical japonica inbred Francis and an elite indica restorer Guanghui 998 (R998). A total of 26 QTLs were detected using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Our study is a first report for exploring genetic architecture of grain yield and grain quality through the combination of association and pedigree-based studies in 16-way MAGIC rice population although several studies reported for yield and grain quality traits 1,3,4,8,9,1113 . Many published studies mentioned that most of high-yielding varieties have longer growth duration for longer metabolic activities and grain filling 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is a first report for exploring genetic architecture of grain yield and grain quality through the combination of association and pedigree-based studies in 16-way MAGIC rice population although several studies reported for yield and grain quality traits 1,3,4,8,9,1113 . Many published studies mentioned that most of high-yielding varieties have longer growth duration for longer metabolic activities and grain filling 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The production of rice has been significantly improved after the development of semi-dwarf cultivars and hybrid rice 3 . However, in the last decades, rice yield was not significantly improved and reached into a projected rice production 4 . To ensure food security, declining in genetic gain, narrow genetic base of the modern rice varieties, biotic and abiotic stress pressure, increasing demand for more quantity and better quality of rice are some of the concerns for rice breeders 2,3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Bin map refers to a certain number of continuous SNP as the unit for determining recombination events, and the parent source of each Bin is speculated to obtain the genome-wide physical map of the offspring. For example, a high-density genetic map consisting of 3016 bin was constructed and finally 26 QTL for six yield traits were located, among which two novel QTL, qAGB6 and qHI9, were identified [20]. In another report, a total of 79 QTL for 15 yield traits were mapped using a high-density linkage map with 3569 bin markers [21].…”
Section: Subject Areasmentioning
confidence: 99%
“…Tang and colleagues characterized the genome‐wide SNPs of the parental varieties of recombinant inbred line (RIL) populations using the high‐throughput GBS and identified a QTL containing the locus Os4g48460 (a putative cytochrome P450) related to rice seed size (Tang et al, 2016). Zhu performed QTL mapping in a restorer line of hybrid rice based on ultra‐high‐density SNP mapping and found 26 QTLs for six yield traits, in which nine QTL alleles presented a significant effect (Zhu et al, 2017). Jiang performed the high‐density genetic map in the QTL mapping of 124 rice backcrossed recombinant inbred lines and showed six QTLs related to seed germination in response to the cold stress (Jiang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%